On universal butterfly and antisymmetric magnetoresistances - Wu, H. T.; Min, Tai; Guo, Z. X.; Wang, X. R. (Frontiers in Physics, 2022)
Butterfly magnetoresistance (BMR) and antisymmetric magnetoresistance (ASMR) are about a butterfly-cross curve and a curve with one peak and one valley when a magnetic field is swept up and down along a fixed direction. Other than the parallelogram-shaped magnetoresistance-curve (MR-curve) often observed in magnetic memory devices, BMR and ASMR are two ubiquitous types of MR-curves observed in diversified magnetic systems, including van der Waals materials, strongly correlated systems, and traditional magnets. Here, we reveal the general principles and the picture behind the BMR and the ASMR that do not depend on the detailed mechanisms of magnetoresistance: 1) The systems exhibit hysteresis loops, common for most magnetic materials with coercivities. 2) The magnetoresistance of the magnetic structures in a large positive magnetic field and in a large negative magnetic field is approximately the same. With the generalized Ohm's law in magnetic materials, these principles explain why most BMR appears in the longitudinal resistance measurements and is very rare in the Hall resistance measurements. Simple toy models, in which the Landau-Lifshitz-Gilbert equation governs magnetization, are used to demonstrate the principles and explain the appearance and disappearance of BMR in various experiments. Our finding provides a simple picture to understand magnetoresistance-related experiments.